Reaching the Right People: Reflexive Practice to Support Effective Recruitment, Participation, and Engagement in Research With Communities Affected by Stigma. Issue 1 (14th December 2018) - Stevenson, Jacqui; Keogh, Peter; Smith, John; West, Elizabeth
Recruiting participants to qualitative studies is often a challenge—reaching the right people, and the right people choosing to participate, is a primary consideration for researchers. For research on HIV, as a condition which continues to be stigmatized, this can be magnified. However, being part of the HIV voluntary sector and occupying a role of "HIV advocate" can provide routes to overcome this challenge. Using the example of the researcher's transition from voluntary sector worker to academic PhD researcher, this article explores how recruitment can be facilitated by utilizing personal and professional networks and how, in turn, this can present new challenges in reaching participants who are not "research regulars, " who are experienced in participating in qualitative research. It further explores reflexive methodologies as applied to participatory research on HIV and aging as it affects women in the UK and asks how the roles of "advocate" and "researcher" complement and challenge one another. Reflexive practice and an analysis of the researcher's motives and how this impacts on recruitment, participation, and dissemination are considered. A three-part approach to reflexively engaging with participants' questions is put forward. This provides a new perspective on participatory approaches in relation to research recruitment specifically.